Numerical and Physical Investigation of the Performance of Turbulence Modeling Schemes around a Scour Hole Downstream of a Fixed Bed Protection - Thi Hoang Thao Nguyen (Water, 2018)
Local scour occurs around hydraulic structures such as piers, bed protections, and dikes. In this study, the turbulent flow around a scour hole downstream of a fixed bed protection was investigated. Numerical modeling with OpenFOAM was applied to compute the flow velocity and turbulent kinetic energy with respect to flow conditions by changing water depth. A proper computational grid size and time step for simulations are suggested. Three typical turbulent models, k − ε , k − ω , and k − ω S S T , were considered for simulating the flow around a scour hole. The performances of the three models were evaluated by comparing them with numerical and laboratory experimental results. Mean flow velocity profiles computed by the three turbulent schemes are generally in good agreement with laboratory measurements. However, k − ω has a limitation in simulating reversal flow in the scour hole, and the k − ε model does not predict turbulent kinetic energy well near the bottom. Thus, this study found that the most suitable turbulent model for simulating flow around a scour hole downstream of a fixed bed protection is the k − ω S S T model.